Positive electrode material and preparation method thereof, positive electrode plate, lithium battery and vehicle
By using the inner core structure and spinel cladding design in high-nickel ternary materials, the problems of lithium-nickel mixed displacement, phase transition and side reactions at high voltage are solved, and the stability and safety of the positive electrode material are improved.
Patent Information
- Application Number
- CN202311243186.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-25
- Publication Date
- 2025-03-25
AI Technical Summary
Existing high-nickel ternary materials are prone to lithium-nickel mixed discharge, phase transition and side reactions with electrolyte at high voltages, resulting in structural instability and safety problems.
The positive electrode material with an outer core structure of the core material is Li1+pNixCoyMnzM(1-x-y-z)O2-q. The Ni element content gradually decreases from the core to the outer surface, the Mn element content gradually increases from the core to the outer surface, and a spinel structure cladding is set on the outer surface of the core.
Effectively reduce lithium-nickel mixed discharge, phase transition and side reaction with electrolyte, improve the stability of the positive electrode material at high voltage, and meet the requirements of cycling performance and safety performance.
Smart Images

Figure CN119695092A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium batteries, and in particular to a positive electrode material and a preparation method thereof, a positive electrode sheet, a lithium battery and a vehicle. Background Art
[0002] Lithium-ion batteries are widely used in many fields such as mobile electronic devices, power tools and electric vehicles due to their advantages such as low self-discharge, high energy density and no memory effect. The performance of lithium-ion batteries is mainly determined by the quality of the positive electrode material. Currently, ternary materials are one of the most widely used positive electrode materials in power batteries.
[0003] With the continuous advancement of science and technology, the market has put forward higher requirements for the energy density, cycle and safety performance of ternary materials, that is, ternary materials with higher nickel content and higher voltage resistance. Although the specific capacity of high-nickel ternary materials is high, the lithium-nickel mixing is serious, which affects the rate performance and capacity. At higher voltages, as more lithium ions are released from the lattice, the structure will become unstable, changing from layered to spinel and rock salt structures, and releasing hydrogen and oxygen, accelerating the reaction with the electrolyte, causing the internal structure to collapse, and even causing thermal runaway, affecting the service life and safety of high-voltage ternary materials.
[0004] Therefore, providing a positive electrode material with a high nickel content, reducing the lithium-nickel mixing, phase change and side reactions with the electrolyte in the positive electrode material, and ensuring the stability of the positive electrode material under high voltage have become key issues. Summary of the invention
[0005] The purpose of this application is to provide a positive electrode material and a preparation method thereof, a positive electrode plate, a lithium battery and a vehicle, which can effectively reduce lithium-nickel mixing, phase change and side reactions with the electrolyte, and can also improve the stability under high voltage to meet the requirements of cycle performance and safety performance.
[0006] To achieve the purpose of this application, this application provides the following technical solutions:
[0007] In a first aspect, the present application provides a positive electrode material, including a core and a coating layer, wherein the chemical formula of the material in the core includes: Li 1+p Ni x Co y Mn z M (1-x-y-z) O 2-q, wherein, -0.1≤p≤0.1, 0.5≤x≤0.95, 0≤y≤0.20, 0.05≤z≤0.30, 1-xyz≥0, 0≤q≤0.05, M is one or more of Mg, Al, W, Zr, Y, Ti, Cr, La, and V; the Ni element content gradually decreases from the core to the outer surface, and the Mn element content gradually increases from the core to the outer surface; the coating layer is coated on the outer surface of the inner core, and the coating layer is a spinel structure.
[0008] In one embodiment, 1-xyz>0, and the content of the M element gradually increases from the core to the outer surface.
[0009] In one embodiment, the chemical formula of the material in the coating layer includes: LiNi 0.5-m Mn 1.5-n A m+n O 4-δ , wherein 0≤m≤0.1, 0≤n≤0.3, 0≤δ≤0.3, and A is one or more of Co, Cr, Fe, Mg, Al, Cu, Zn, Zr, Si, La, Y, Sc, Sm, and Ce.
[0010] In one embodiment, the Ni content in the coating layer is less than or equal to the Ni content at the outer surface of the inner core.
[0011] In one embodiment, the Mn element content in the coating layer is greater than or equal to the Mn element content at the outer surface of the inner core.
[0012] In one embodiment, the content of element A in the coating layer is greater than or equal to the content of element M at the outer surface of the inner core.
[0013] In one embodiment, the coating layer has a thickness of 1 nm to 200 nm.
[0014] In one embodiment, the mass fraction of the coating layer is 0.1% to 10%.
[0015] In one embodiment, the particle size D50 of the positive electrode material is 2 μm to 15 μm.
[0016] In a second aspect, the present application provides a method for preparing a positive electrode material, comprising: mixing a first solution into a second solution, and mixing the second solution into a third solution to obtain a precursor solution; pretreating the precursor solution to obtain a precursor solid; grinding and sintering the precursor solid and a lithium source to obtain primary particles; mixing the primary particles with a fourth solution, and obtaining a positive electrode material with a coating layer after drying and calcining; wherein the first solution includes Ni and Mn elements, the second solution includes Ni element, and the third solution includes a precipitant and a complexing agent; the Ni element content in the first solution is lower than the Ni element content in the second solution, and the Mn element content in the first solution is higher than the Mn element content in the second solution.
[0017] In one embodiment, the first solution and the second solution also include element M, wherein element M is one or more of Mg, Al, W, Zr, Y, Ti, Cr, La, and V; and the content of element M in the first solution is greater than the content of element M in the second solution.
[0018] In a third aspect, the present application provides a positive electrode plate, the positive electrode plate comprising a current collector and an active material layer disposed on the current collector, the active material layer comprising the positive electrode material as described in any one of the embodiments of the first aspect.
[0019] In a fourth aspect, the present application provides a lithium battery, comprising a separator, a negative electrode sheet and the positive electrode sheet described in the third aspect, wherein the positive electrode sheet, the separator and the negative electrode sheet are stacked in sequence.
[0020] In a fifth aspect, the present application provides a vehicle, comprising the lithium battery described in the fourth aspect.
[0021] The positive electrode material provided in the present application can effectively reduce the lithium-nickel mixing, phase change and side reactions with the electrolyte on the outer surface of the inner core by controlling the changes in the content of nickel and manganese elements in the inner core, while meeting the requirements of the positive electrode material being able to maintain a relatively high specific capacity; at the same time, by providing a spinel structured coating layer on the outer surface of the inner core, not only can the inner core be further protected, but also the stability of the positive electrode material under high voltage can be improved, thereby meeting the requirements of cycle performance and safety performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0023] Figure 1 is a schematic diagram of a cross-sectional structure of a positive electrode material according to an embodiment;
[0024] Figure 2 is a schematic diagram of the changing trend of elements in the kernel of an implementation mode;
[0025] Figure 3 The present invention is a flow chart of a method for preparing a positive electrode material according to an embodiment. DETAILED DESCRIPTION
[0026] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0027] It should be noted that when a component is said to be "fixed to" another component, it can be directly on the other component or there can be a central component. When a component is said to be "connected to" another component, it can be directly connected to the other component or there can be a central component at the same time.
[0028] Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used in this application and in the specification are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "and / or" used in this application includes any and all combinations of one or more of the related listed items.
[0029] In conjunction with the accompanying drawings, some embodiments of the present application are described in detail below. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.
[0030] In the first aspect, the present application provides a positive electrode material, please refer to Figure 1 , including a core 10 and a coating layer 20. The chemical formula of the material in the core 10 includes: Li 1+p Ni x Co y Mn z M (1-x-y-z) O 2-q, wherein, -0.1≤p≤0.1, 0.5≤x≤0.95, 0≤y≤0.20, 0.05≤z≤0.30, 1-xyz≥0, 0≤q≤0.05, M is one or more of Mg, Al, W, Zr, Y, Ti, Cr, La, and V; the Ni element content gradually decreases from the core to the outer surface, and the Mn element content gradually increases from the core to the outer surface; the coating layer 20 is coated on the outer surface of the inner core 10, and the coating layer 20 is a spinel structure.
[0031] Optionally, the positive electrode material is spherical or quasi-spherical. Therefore, the shape of the core 10 can also be spherical or quasi-spherical. Therefore, the change of the increase or decrease of the elements mentioned above should be understood as the change of the radius of the core 10, the content of the Ni element is different at different radii, and the content of the Mn element is also different.
[0032] Optionally, the specific reduction trend can be an irregular reduction or a gradient reduction. For example, please refer to Figure 2 , the horizontal axis represents the distance H from the core 10 to the outer surface, and the vertical axis represents the content of Ni element T. A is a straight line, so the content of Ni element increases uniformly with the change of the distance from the core to the outer surface; B is a curve, so the content of Ni element increases non-uniformly and irregularly with the change of the distance from the core to the outer surface.
[0033] It is understandable that the total content of Ni and Mn will not change in the present application, and only the distribution of Ni and Mn elements is controlled during the preparation process. Thus, the part with high nickel content is arranged at the core of the core 10, and more manganese elements are arranged at the outer surface of the core 10, so as to reduce the lithium-nickel mixing phenomenon at the outer surface of the core 10 and the side reaction caused by direct contact between the nickel element and the electrolyte, further inhibit the phase change, hydrogen production, oxygen production and other processes, so that the rate, cycle and safety performance of the positive electrode material can be effectively improved.
[0034] Optionally, the coating layer 20 is a spinel structure. The coating layer 20 is uniformly coated on the outer surface of the core 10. Because the coating layer 20 with a spinel structure has excellent high voltage resistance and can provide some active lithium, the upper limit voltage and energy density of the battery can be improved by setting the coating layer 20; at the same time, the coating layer 20 with a spinel structure can also provide a lithium ion channel during the charge and discharge process, improve the conductivity of the ions, and its stable structural characteristics can inhibit the changes in the material structure during the charge and discharge process.
[0035] Optionally, the coating layer 20 is in-situ generated on the outer surface of the core 10 by a wet chemical method. The advantage is that the in-situ generated coating layer 20 is well bonded to the core 10, and when the material of the coating layer 20 and the material of the core 10 are similar in lattice, the mismatch stress of the coating layer 20 is small, so the coating layer 20 is not easy to break or fall off.
[0036] Therefore, the positive electrode material provided in the present application, by controlling the changes in the contents of nickel and manganese elements in the core 10, can effectively reduce the lithium-nickel mixing, phase change and side reactions with the electrolyte occurring on the outer surface of the core 10, while satisfying the requirement of maintaining a relatively high specific capacity of the positive electrode material; at the same time, by providing a spinel-structured coating layer 20 on the outer surface of the core 10, not only can the core 10 be further protected, but also the stability of the positive electrode material under high voltage can be improved, thereby satisfying the requirements of cycle performance and safety performance.
[0037] In one embodiment, in the chemical formula mentioned in the above embodiment, 1-xyz>0, and the content of the M element gradually increases from the core to the outer surface.
[0038] Specifically, the core 10 is also doped with M element (or M ion, hereinafter referred to as M element), and the M element is the metal element mentioned above. The M element can enhance the ionic conductivity of the core 10 material, thereby improving the cycle and rate discharge performance of the positive electrode material; at the same time, the setting of the M element is also beneficial to stabilize the lattice structure of the core 10, ensuring the structural stability of the positive electrode material during the charging and discharging process.
[0039] Optionally, the content of the M element gradually increases from the core to the outer surface, and the specific rules of the increase can refer to the examples in the above-mentioned embodiments. It can be understood that when there are more M elements on the outer surface of the inner core 10, the metal cations formed by the M elements can firmly stabilize the lattice structure of the outermost layer, and can avoid side reactions at the interface where the inner core 10 contacts the electrolyte, and avoid structural collapse inward from the outer surface, thereby improving the structural stability of the positive electrode material; at the same time, due to the reduction of side reactions between the inner core 10 and the electrolyte, the capacity attenuation problem of the positive electrode material can also be effectively alleviated, and the cycle performance of the positive electrode material can be improved.
[0040] In one embodiment, the coating layer 20 is in-situ generated by a wet chemical method, and the chemical formula of the material in the coating layer 20 includes: LiNi 0.5-m Mn 1.5 -nA m+n O 4-δ , wherein 0≤m≤0.1, 0≤n≤0.3, 0≤δ≤0.3, and A is one or more of Co, Cr, Fe, Mg, Al, Cu, Zn, Zr, Si, La, Y, Sc, Sm, and Ce.
[0041] By in-situ generating a coating layer 20 of a spinel structure on the outer surface of the core 10, compared with the traditional coating method, the coating layer 20 obtained by this method is more uniform, and the core 10 particles and the coating layer 20 are more tightly bonded, and the process is simple, the equipment requirements are low, the cost is relatively low, and it is suitable for industrial production. The advantage of using the above materials as the coating layer 20 is that the lattices of the two are close, so that the mismatch stress is small; the coating layer 20 can also provide some active lithium and lithium ion channels.
[0042] In one embodiment, the Ni content in the coating layer 20 is less than or equal to the Ni content on the outer surface of the core 10. It is understandable that although the core 10 and the coating layer 20 have similar material structures, due to different preparation methods, the core 10 and the coating layer 20 should actually have two structures.
[0043] Optionally, the Ni element in the coating layer 20 should be evenly distributed. Therefore, in order to prevent the lithium-nickel mixing phenomenon in the entire positive electrode material, the Ni element in the coating layer 20 is set to be no greater than the Ni element content at the outer surface of the core 10. In this way, it can be ensured that the coating layer 20 in direct contact with the electrolyte will not be mixed with lithium and nickel, thereby ensuring the stability of the coating layer 20 structure.
[0044] In one embodiment, the Mn content in the coating layer 20 is greater than or equal to the Mn content at the outer surface of the core 10. The Mn content in the coating layer 20 is controlled to ensure that the nickel-manganese ratio in the coating layer 20 is appropriate.
[0045] In one embodiment, the content of the A element in the coating layer 20 is greater than or equal to the content of the M element at the outer surface of the core 10 .
[0046] Optionally, the A element in the coating layer 20 may be the same as or different from the M element in the core 10. Among them, the advantage of the same A element and M element is that the preparation cost of the positive electrode material is controllable, and there is no need to introduce other different metal materials. The advantage of the different A element and M element is that the M element in the coating layer 20 may migrate to the outer surface of the core 10, thereby forming multi-element doping in the core 10, and the A element and the M element may have different atomic radii, which is conducive to adjusting the structural stability of the core 10.
[0047] In one embodiment, the coating layer 20 has a thickness of 1 nm to 200 nm. Specifically, the thickness of the coating layer 20 may be, but is not limited to, 1 nm, 10 nm, 20 nm, 50 nm, 80 nm, 100 nm, 150 nm, and 200 nm. By setting the thickness of the coating layer 20 within the above range, the capacity of the positive electrode material can be ensured. When the coating layer 20 is too thick, the initial capacity loss of the positive electrode material will be too large, and when the coating layer 20 is too thin, the coating will not be sufficient and will not provide an ideal protective effect.
[0048] In one embodiment, the mass fraction of the coating layer 20 is 0.1% to 10%. Specifically, the mass fraction of the coating layer 20 in the positive electrode material may be, but is not limited to, 0.1%, 0.3%, 0.5%, 0.7%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%. By setting the mass fraction of the coating layer 20 within the above range, the capacity of the positive electrode material can be ensured. When the coating layer 20 is too much, the initial capacity loss of the positive electrode material will be too large, and when the coating layer 20 is too little, the coating will not be sufficient and the ideal protection effect cannot be achieved.
[0049] In one embodiment, the particle size D50 of the positive electrode material is 2 μm to 15 μm. Specifically, the particle size of the positive electrode material may be, but is not limited to, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, and 15 μm. When the particle size of the positive electrode material is smaller than the above range, it is easy to cause the overall size of the positive electrode material to be smaller, and the particles will form a relatively serious agglomeration; when the particle size of the positive electrode material is larger than the above range, the specific surface area of the positive electrode material is reduced, which reduces the efficiency of lithium ion insertion and extraction.
[0050] In the second aspect, the present application also provides a method for preparing a positive electrode material, please refer to Figure 3 , including the following steps:
[0051] Step S1, mixing the first solution into the second solution, and mixing the second solution into the third solution, so as to obtain a precursor solution.
[0052] Step S2, pre-treating the precursor solution to obtain a precursor solid.
[0053] Step S3, grinding and sintering the precursor solid and the lithium source to obtain primary particles.
[0054] Step S4, mixing the primary particles with the fourth solution, and obtaining a positive electrode material with a coating layer after drying and calcining.
[0055] Specifically, in step S1, the first solution is a Ni / Co / Mn / M solution with a low Ni content; the second solution is a Ni / Co / M solution or a Ni / Co / Mn / M solution with a high Ni content; the third solution includes a precipitant (hydroxide) and a complexing agent (ammonia water), wherein the Ni element content in the first solution is lower than the Ni element content in the second solution, and the Mn element content in the first solution is higher than the Mn element content in the second solution.
[0056] Optionally, the content of the M element in the first solution is greater than the content of the M element in the second solution.
[0057] Optionally, step S1 should specifically include: continuously pumping the first solution into a container containing the second solution and continuously stirring, and continuously pumping the second solution into a reactor containing the third solution, heating the reactor and introducing a protective atmosphere, adjusting the ammonia concentration of the reaction system with ammonia water, adjusting the pH value of the reaction system with a hydroxide precipitant solution, stirring for a co-precipitation reaction, and obtaining a precursor solution.
[0058] Optionally, in step S1, the feeding speed of the first solution is 20mL / h to 60mL / h, and the feeding speed of the second solution is 50mL / h to 100mL / h. Meeting the above speeds can ensure the quality of the formed precursor. If the feeding speed is too fast, it is not conducive to controlling the pH value of the reaction solution and the growth rate of the particles, because a large amount of metal ions combined with the hydroxide precipitant will precipitate quickly, and the pH value drops rapidly; if the feeding speed is too slow, it is not conducive to improving production efficiency.
[0059] Optionally, in step S1, the concentration of metal ions in the first solution is 0.5 mol / L to 6 mol / L; wherein the molar percentage of Ni in the total metal ions is 40% to 70%, the molar percentage of Co in the total metal ions is 5% to 40%, the molar percentage of Mn in the total metal ions is 20% to 50%, and the molar percentage of M in the total metal ions is 0% to 10%; therefore, the sum of Ni, Co, Mn, and M ions is 100%.
[0060] Optionally, in step S1, the concentration of metal ions in the second solution is 0.5 mol / L to 6 mol / L; wherein the molar percentage of Ni in the total metal ions is 60% to 95%, the molar percentage of Co in the total metal ions is 5% to 40%, the molar percentage of Mn in the total metal ions is 0% to 30%, and the molar percentage of M in the total metal ions is 0% to 10%; therefore, the sum of Ni, Co, Mn, and M ions is 100%.
[0061] Optionally, in step S1, the first solution and the second solution are mixed solutions of soluble nickel salt, soluble cobalt salt, soluble M salt and soluble manganese salt.
[0062] Optionally, in step S1, the soluble nickel salt is one or more of nickel sulfate, nickel nitrate, nickel acetate, nickel chloride and hydrates thereof.
[0063] Optionally, in step S1, the soluble cobalt salt is one or more of cobalt sulfate, cobalt nitrate, cobalt acetate, cobalt chloride and hydrates thereof.
[0064] Optionally, in step S1, M is one or more of Mg, Al, W, Zr, Y, Ti, Cr, La, and V, and the soluble M salt is one or more of sulfuric acid M, nitric acid M, acetic acid M, chloride M, and hydrates thereof.
[0065] Optionally, in step S1, the soluble manganese salt is one or more of manganese sulfate, manganese nitrate, manganese acetate, manganese chloride and hydrates thereof.
[0066] Optionally, in step S1, the molar concentration of the ammonia solution (third solution) is 1.0 mol / L to 7.0 mol / L. If the molar concentration of the ammonia solution is too low, it is difficult to completely complex the metal ions, and if the molar concentration of the ammonia solution is too high, it is not conducive to the metal ions forming hydroxide precipitation.
[0067] Optionally, in step S1, the reaction kettle is heated to 30°C to 70°C.
[0068] Optionally, in step S1, the protective atmosphere is a nitrogen atmosphere and / or an argon atmosphere, etc.
[0069] Optionally, in step S1, the concentration of ammonia in the reaction system (third solution) is adjusted to be maintained at 1.0 mol / L to 7.0 mol / L with ammonia. It is understandable that since the second solution is continuously added to the third solution, the concentration of ammonia changes with the addition of the second solution, so in order to ensure that the concentration of ammonia is within the required range, it is necessary to continuously add high-concentration ammonia.
[0070] Optionally, in step S1, the mass concentration of ammonia water used to adjust the ammonia concentration of the reaction system is 20% to 28%.
[0071] Optionally, in step S1, the pH value of the reaction system is adjusted to be maintained at 9-12 using a hydroxide precipitant solution.
[0072] Optionally, in step S1, the molar concentration of the hydroxide precipitant solution is 0.5 mol / L to 10 mol / L.
[0073] Optionally, in step S1, the hydroxide precipitant is one or more of sodium hydroxide, potassium hydroxide or lithium hydroxide.
[0074] Optionally, in step S2, the pretreatment specifically includes but is not limited to the process steps of filtration, washing and drying.
[0075] Optionally, in step S3, the lithium source is one or more of lithium hydroxide, lithium nitrate, lithium carbonate, lithium oxalate or lithium acetate and hydrates thereof.
[0076] Optionally, in step S3, the molar ratio of lithium element in the lithium source to metal element (the sum of Ni, Co, Mn, and M) in the precursor solid is 1.02 to 1.2: 1. If the amount of lithium element added is too low, the lithium element will be insufficient, resulting in a too low discharge specific capacity; if the amount of lithium element added is too high, the proportion of active material will decrease, which will also result in a decrease in discharge specific capacity.
[0077] Optionally, in step S3, sintering includes pre-sintering and formal sintering, and the pre-sintering temperature is 300°C to 600°C and the time is 2h to 10h. The purpose of pre-sintering is to remove the residual water in the nickel-cobalt-manganese ternary precursor and melt the lithium source to mix the materials evenly.
[0078] Optionally, in step S3, the formal sintering temperature is 650°C to 1100°C, and the sintering time is 8h to 24h.
[0079] Optionally, step S4 should specifically be: mixing the primary particles with water and stirring them evenly, then putting them into the reactor, then flowing the nickel-manganese binary salt solution, A salt solution and precipitant solution into the reactor at a certain proportion and flow rate for coating reaction, and then filtering, washing and calcining to obtain a coated product; then sintering the coated product in air or oxygen atmosphere for 2h to 15h, controlling the sintering temperature at 500℃ to 1100℃, cooling and crushing to obtain the final positive electrode material.
[0080] Optionally, in step S4, A is one or more of Co, Cr, Fe, Mg, Al, Cu, Zn, Zr, Si, La, Y, Sc, Sm, and Ce, and the nickel-manganese binary salt solution and the A salt solution are a mixed solution of a soluble nickel salt and a soluble manganese salt, and a soluble A salt, respectively.
[0081] Optionally, in step S4, the precipitant is one or more of soluble carbonates, soluble oxalates, sodium hydroxide, potassium hydroxide, and the like.
[0082] Optionally, in step S4, the reaction temperature during the coating process is 40°C to 90°C, and the reaction time is 2h to 10h.
[0083] The positive electrode material prepared by the above method has a controllable change in the content of nickel and manganese elements (increase or decrease), which can effectively reduce the lithium-nickel mixing, phase change and side reaction with the electrolyte on the outer surface of the inner core under the premise of meeting the requirement of maintaining a high specific capacity of the positive electrode material; at the same time, by setting a coating layer, not only can the inner core be further protected, but also the stability of the positive electrode material under high voltage can be improved to meet the requirements of cycle performance and safety performance. Moreover, the method provided by the present application is simple in process, low in cost, and suitable for industrial production.
[0084] In a third aspect, the present application further provides a positive electrode plate, the positive electrode plate comprising a current collector and an active material layer disposed on the current collector, the active material layer comprising the positive electrode material of any one of the second aspects.
[0085] Optionally, the current collector includes any one of copper foil and aluminum foil.
[0086] Optionally, the active material layer includes a positive electrode material, a binder and a conductive agent.
[0087] Optionally, the binder includes one or more of polyvinylidene chloride, soluble polytetrafluoroethylene, styrene-butadiene rubber, hydroxypropyl methylcellulose, methylcellulose, carboxymethyl cellulose, polyvinyl alcohol, acrylonitrile copolymer, sodium alginate, chitosan and chitosan derivatives.
[0088] Optionally, the conductive agent includes one or more of graphite, carbon black, acetylene black, graphene, carbon fiber, C60 and carbon nanotubes.
[0089] In a fourth aspect, the present application further provides a lithium battery, comprising a positive electrode sheet, a negative electrode sheet and a separator. The positive electrode sheet, the separator and the negative electrode sheet are stacked in sequence. The negative electrode sheet can be a graphite negative electrode sheet, a negative lithium electrode sheet, etc.
[0090] In a fifth aspect, the present application also provides a vehicle, the vehicle comprising the lithium battery of the fourth aspect.
[0091] The technical solution of the present invention is described in detail below through specific embodiments.
[0092] Embodiment 1:
[0093] The positive electrode material is LiNi 0.5 Mn 1.5 O 4 @LiNi 0.80 Co 0.05 Mn 0.15 O 2 , LiNi 0.5 Mn 1.5 O 4 The coating layer of spinel, LiNi 0.80 Co0.05 Mn 0.15 O 2 The inner core has a Ni content that gradually decreases from the inner core to the outer surface, a Mn content that gradually increases from the inner core to the outer surface, and a Co content that is uniformly distributed in the particles. The preparation method is as follows:
[0094] (1) 4 L of Ni / Co / Mn solution with low Ni content (a mixed solution of nickel nitrate, cobalt nitrate and manganese nitrate in a molar ratio of 70:5:25, with a total concentration of 2.0 mol / L) was pumped into a container containing 4 L of Ni / Co / Mn solution with high Ni content (a mixed solution of nickel nitrate, cobalt nitrate and manganese nitrate in a molar ratio of 90:5:5, with a total concentration of 2.0 mol / L) (feeding rate of 50 mL / h), and stirred at room temperature.
[0095] At the same time, the Ni / Co / Mn solution with high Ni content was pumped into a reactor containing 4L ammonia solution (concentration of 2mol / L) at a rate of 100mL / h, and high-purity nitrogen was introduced as the protective atmosphere in the reactor, and the temperature was adjusted to maintain continuous stirring at 40°C. At the same time, the concentration of ammonia water was adjusted to 1mol / L with 25% ammonia water, and the pH value of the reaction system was adjusted to 11 with 5mol / L sodium hydroxide solution. A coprecipitation reaction was carried out at 50°C and 1000r / min with continuous stirring to obtain a gradient nickel-cobalt-manganese hydroxide precursor solution.
[0096] (2) The precursor solution obtained in step (1) is kept at 50° C. and stirred for aging for 15 hours. After filtering and washing, it is dried at 60° C. for 24 hours to obtain a gradient nickel-cobalt-manganese hydroxide precursor solid.
[0097] (3) 9.214 g of nickel-cobalt-manganese hydroxide precursor solid obtained in step (2) was mixed with 4.530 g of LiOH-H 2 O after mixed grinding, in a pure oxygen atmosphere, the temperature was first raised to 450°C, sintered for 4 hours, then raised to 750°C, sintered for 12 hours, and cooled to room temperature to obtain primary particles of gradient nickel-cobalt-lithium-manganese oxide ternary material.
[0098] (4) The primary particles obtained in step (3) are mixed with water and stirred evenly, and then put into a reactor, and then the nickel-manganese mixed salt solution (Ni:Mn=1:3) and the carbonate solution are flowed into the reactor to react to obtain carbonate slurry, which is then filtered, washed, and calcined to obtain a coated product. The reaction temperature is controlled at 50° C. and the reaction time is 4 hours during the entire reaction process.
[0099] (5) Sintering the coated product obtained in step (4) in an oxygen atmosphere for 8 hours, controlling the sintering temperature to 850° C., cooling and crushing to obtain the final product.
[0100] Example 2
[0101] The positive electrode material is LiNi 0.5 Mn 1.5 O 4 @LiNi 0.8 Co 0.05 Mn 0.1 Al 0.05 O 2 , LiNi 0.5 Mn 1.5 O 4 The coating layer of spinel, LiNi 0.8 Co 0.05 Mn 0.1 Al 0.05 O 2 The content of Ni in the core gradually decreases from the core to the outer surface, the content of Mn in the core gradually increases from the core to the outer surface of the particle, the content of Co is evenly distributed in the particle, and the content of Al gradually increases from the core to the outer surface of the particle. The preparation method thereof differs from that of Example 1 only in that:
[0102] In step (1), 4L of Ni / Co / Mn / Al solution with low Ni content (a mixed solution of nickel nitrate, cobalt nitrate, manganese nitrate and aluminum sulfate in a molar ratio of 70:5:17:8, with a total concentration of 2.0 mol / L) is pumped into a container containing 4L of Ni / Co / Mn / Al solution with high Ni content (a mixed solution of nickel nitrate, cobalt nitrate, manganese nitrate and aluminum nitrate in a molar ratio of 90:5:3:2, with a total concentration of 2.0 mol / L) (feeding rate is 40 mL / h), and stirred at room temperature, and the rest is the same as in Example 1.
[0103] Example 3
[0104] The positive electrode material is LiNi 0.45 Fe 0.05 Mn 1.5 O 4 @LiNi 0.8 Co 0.05 Mn 0.15 O 2 , LiNi 0.45 Fe 0.05 Mn 1.5 O 4 Spinel coating, LiNi 0.8 Co 0.05 Mn 0.15 O 2 The content of Ni in the core gradually decreases from the core to the outer surface, the content of Mn in the core gradually increases from the core to the outer surface of the particle, the content of Co is evenly distributed in the particle, and the content of Al gradually increases from the core to the outer surface of the particle. The preparation method thereof differs from that of Example 1 only in that:
[0105] In step (4), the nickel-manganese mixed salt solution (Ni:Mn=1:3) is changed to a nickel-iron-manganese mixed salt solution (Ni:Fe:Mn=0.45:0.05:1.5), and the rest is the same as in Example 1.
[0106] Example 4
[0107] The positive electrode material is LiNi 0.45 Cr 0.05 Mn 1.5 O 4 @LiNi 0.8 Co 0.05 Mn 0.1 Mg 0.02 Al 0.03 O 1.99 , LiNi 0.45 Cr 0.05 Mn 1.5 O 4 The coating layer of spinel, LiNi 0.8 Co 0.05 Mn 0.1 Mg 0.02 Al 0.03 O 1.99 The content of Ni in the core gradually decreases from the core to the outer surface, the content of Mn, Mg and Al in the core gradually increases from the core to the outer surface, and the content of Co is evenly distributed in the particles. The difference between the preparation method and Example 1 is that:
[0108] In step (1), 4L of Ni / Co / Mn / Mg / Al solution with low Ni content (a mixed solution of nickel nitrate, cobalt nitrate, manganese nitrate, magnesium nitrate and aluminum sulfate in a molar ratio of 65:5:20:4:6, with a total concentration of 2.0 mol / L) is pumped into a container containing 4L of Ni / Co solution with high Ni content (a mixed solution of nickel nitrate and cobalt nitrate in a molar ratio of 95:5, with a total concentration of 2.0 mol / L) (feeding rate of 40 mL / h), and stirred at room temperature.
[0109] In step (4), the nickel-manganese mixed salt solution (Ni:Mn=1:3) is changed to a nickel-chromium-manganese mixed salt solution (Ni:Cr:Mn=0.45:0.05:1.5), and the rest is the same as in Example 1.
[0110] Example 5
[0111] The positive electrode material is LiNi 0.45 Al 0.05 Mn 1.5 O 4 @LiNi 0.8 Co 0.05 Mn 0.1 Mg0.02 Al 0.03 O 1.99 , LiNi 0.45 Al 0.05 Mn 1.5 O 4 The coating layer of spinel, LiNi 0.8 Co 0.05 Mn 0.1 Mg 0.02 Al 0.03 O 1.99 The content of Ni in the core gradually decreases from the core to the outer surface, the content of Mn, Mg and Al in the core gradually increases from the core to the outer surface, and the content of Co is evenly distributed in the particles. The difference between the preparation method and Example 1 is that:
[0112] In step (1), 4L of Ni / Co / Mn / Mg / Al solution with low Ni content (a mixed solution of nickel nitrate, cobalt nitrate, manganese nitrate, magnesium nitrate and aluminum sulfate in a molar ratio of 65:5:20:4:6, with a total concentration of 2.0 mol / L) is pumped into a container containing 4L of Ni / Co solution with high Ni content (a mixed solution of nickel nitrate and cobalt nitrate in a molar ratio of 95:5, with a total concentration of 2.0 mol / L) (feeding rate of 40 mL / h), and stirred at room temperature.
[0113] In step (4), the nickel-manganese mixed salt solution (Ni:Mn=1:3) is changed to a nickel-aluminum-manganese mixed salt solution (Ni:aluminum:Mn=0.45:0.05:1.5), and the rest is the same as in Example 1.
[0114] Comparative Example 1
[0115] The difference between this comparative example and Example 1 is only that:
[0116] In step (1), 4 L of Ni / Co / Mn solution with low Ni content and 4 L of Ni / Co / Mn solution with high Ni content are directly mixed. Then, the mixed solution is pumped into ammonia water to obtain a uniformly distributed nickel-cobalt-manganese ternary positive electrode material precursor, and the rest is the same as in Example 1.
[0117] Comparative Example 2
[0118] The difference between this comparative example and Example 1 is only that:
[0119] No coating layer was provided (steps (4) and (5) in Example 1 were not performed), and the remainder was the same as in Example 1.
[0120] The positive electrode materials provided in the above-mentioned Examples 1-4 and the positive electrode materials provided in Comparative Examples 1-2 are respectively assembled into positive electrode sheets and lithium batteries according to the following methods:
[0121] The positive electrode material obtained above is used to prepare a positive electrode sheet, and the negative electrode sheet is a lithium sheet. The positive electrode sheet and the negative electrode sheet are assembled into a button battery, in which the conductive agent is super "p", the separator is Celgard2500, and the electrolyte is 1 mol / L LiPF 6 Conductive salt and solvent of DMC:DEC:EC (wt %)=1:1:1.
[0122] Electrochemical testing:
[0123] The lithium batteries prepared in the above-mentioned embodiments and comparative examples were subjected to rate and cycle performance tests.
[0124] The rate performance test conditions are: room temperature, charge and discharge voltage range of 2.70-4.40V, 0.02C constant current charging to a cut-off voltage of 4.4V, then constant voltage charging to a cut-off current of 0.05C, and discharging at 1 / 3C or 5C to 2.7V.
[0125] The cycle performance test conditions are: room temperature, charge and discharge voltage range of 2.70-4.40V, 1C constant current charging to a cut-off voltage of 4.4V, then constant voltage charging to a cut-off current of 0.05C, discharging at 1C to 2.7V, and the number of cycles is 200 times.
[0126] The test results are shown in Table 1.
[0127] Table 1
[0128]
[0129] From the test results in Table 1, it can be seen that the LiNi 0.5 Mn 1.5 O 4 Gradient LiNi coating 0.80 Co 0.05 Mn 0.15 O 2 The discharge capacity is as high as 210.9 mAh / g at 1 / 3C, and 180.3 mAh / g at 5C, with good rate performance. The first discharge capacity is 206.2 mAh / g at 1C, and the capacity retention rate is 89.3% after 200 cycles, indicating good cycle performance. The LiNi 0.5 Mn 1.5 O 4 Gradient LiNi coating 0.8 Co 0.05 Mn 0.1 Al 0.05 O 2The discharge capacity is as high as 211.5 mAh / g at 1 / 3C and 183.5 mAh / g at 5C, with excellent rate performance. The first discharge capacity is 207.5 mAh / g at 1C, and the capacity retention rate is 90.8% after 200 cycles. The cycle performance is slightly better than that of the sample without Al doping in the core of Example 1. 0.45 Fe 0.5 Mn 1.5 O 4 Gradient LiNi coating 0.8 Co 0.05 Mn 0.15 O 2 The discharge capacity is as high as 211.1 mAh / g at 1 / 3C and 180.6 mAh / g at 5C, with good rate performance. The first discharge capacity is 205.6 mAh / g at 1C, and the capacity retention rate is 91.2% after 200 cycles. The cycle performance is significantly better than that of the sample without Fe doping in the coating layer of Example 1. 0.45 Cr 0.5 Mn 1.5 O 4 Gradient LiNi coating 0.8 Co 0.05 Mn 0.1 Mg 0.02 Al 0.03 O 2 The discharge specific capacity is as high as 211.8 mAh / g at 1 / 3C, 184.3 mAh / g at 5C, and 207.9 mAh / g at 1C. The capacity retention rate is 92.0% after 200 cycles. The rate performance and cycle performance are greatly improved compared with Example 1.
[0130] Comparative Example 1 is LiNi 0.5 Mn 1.5 O 4 LiNi coating evenly distributed 0.80 Co 0.05 Mn 0.15 O 2 The rate performance is close to that of Example 1, but the capacity retention rate is only 81.5% after 200 cycles at 1C, and the cycle performance is poor, indicating that the nickel-cobalt-manganese ternary material without nickel-manganese gradient distribution is prone to lithium-nickel mixing and phase change on the surface under high pressure, and the cycle stability is significantly deteriorated. 0.80 Co 0.05 Mn 0.15 O 2Due to the absence of surface coating, the discharge capacity at 1 / 3C is slightly higher than that of Example 1, but only 155.1 mAh / g is discharged at 5C, and the rate performance is significantly reduced. After 500 cycles at 1C, the capacity retention rate is much lower than that of Example 1, only 64.3%, and the cycle performance is extremely poor, indicating that there is no LiNi 0.5 Mn 1.5 O 4 The rate performance of the nickel-cobalt-manganese ternary material is reduced due to the coating layer, and the surface is prone to phase change, decomposition, cracking and side reactions with the electrolyte under high voltage. The cycle stability is greatly attenuated and the life is severely shortened.
[0131] In the description of the embodiments of the present application, it should be noted that the orientation or positional relationship of terms such as "center", "up", "down", "left", "right", "vertical", "horizontal", "inside" and "outside" are based on the orientation or positional relationship described in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present application.
[0132] What is disclosed above is only a preferred embodiment of the present application, and it certainly cannot be used to limit the scope of rights of the present application. Ordinary technicians in this field can understand that all or part of the processes of implementing the above embodiment and equivalent changes made according to the claims of the present application are still within the scope covered by the present application.
Claims
1. A positive electrode material, characterized in that: include: The core, wherein the chemical formula of the material in the core includes: Li 1+p Ni x Co y Mn z M (1-x-y-z) O 2-q , wherein, -0.1≤p≤0.1, 0.5≤x≤0.95, 0≤y≤0.20, 0.05≤z≤0.30, 1-xyz≥0, 0≤q≤0.05, M is one or more of Mg, Al, W, Zr, Y, Ti, Cr, La, V; the Ni content gradually decreases from the core to the outer surface, and the Mn content gradually increases from the core to the outer surface; The coating layer is coated on the outer surface of the inner core, and the coating layer is a spinel structure.
2. The positive electrode material according to claim 1, characterized in that 1-xyz>0, the content of M element gradually increases from the core to the outer surface.
3. The positive electrode material according to claim 1, characterized in that The chemical formula of the material in the coating layer includes: LiNi 0.5-m Mn 1.5-n A m+n O 4-δ , wherein 0≤m≤0.1, 0≤n≤0.3, 0≤δ≤0.3, and A is one or more of Co, Cr, Fe, Mg, Al, Cu, Zn, Zr, Si, La, Y, Sc, Sm, and Ce.
4. The positive electrode material according to claim 3, characterized in that The Ni content in the coating layer is less than or equal to the Ni content at the outer surface of the core.
5. The positive electrode material according to claim 3, characterized in that The Mn element content in the coating layer is greater than or equal to the Mn element content at the outer surface of the core.
6. The positive electrode material according to claim 3, characterized in that The content of element A in the coating layer is greater than or equal to the content of element M at the outer surface of the inner core.
7. The positive electrode material according to claim 3, characterized in that The coating layer has a thickness of 1 nm to 200 nm.
8. The positive electrode material according to claim 3, characterized in that The mass fraction of the coating layer is 0.1% to 10%.
9. The positive electrode material according to claim 1, characterized in that The particle size D50 of the positive electrode material is 2 μm to 15 μm.
10. A method for preparing a positive electrode material, characterized in that: include: mixing the first solution into the second solution, and simultaneously mixing the second solution into the third solution, thereby obtaining a precursor solution; Pre-treating the precursor solution to obtain a precursor solid; Grinding and sintering the precursor solid and the lithium source to obtain primary particles; The primary particles are mixed with a fourth solution, and after drying and calcining, a positive electrode material having a coating layer is obtained; Among them, the first solution includes Ni and Mn elements, the second solution includes Ni, and the third solution includes a precipitant and a complexing agent; the Ni content in the first solution is lower than the Ni content in the second solution, and the Mn content in the first solution is higher than the Mn content in the second solution.
11. The preparation method according to claim 10, characterized in that: The first solution and the second solution also include element M, wherein element M is one or more of Mg, Al, W, Zr, Y, Ti, Cr, La, and V; and the content of element M in the first solution is greater than the content of element M in the second solution.
12. A positive electrode sheet, characterized in that: The positive electrode sheet comprises a current collector and an active material layer disposed on the current collector, and the active material layer comprises the positive electrode material according to any one of claims 1 to 9.
13. A lithium battery, characterized in that: The lithium battery comprises a separator, a negative electrode sheet and the positive electrode sheet according to claim 12, wherein the positive electrode sheet, the separator and the negative electrode sheet are stacked in sequence.
14. A vehicle, characterized in that: The vehicle includes the lithium battery of claim 13.